Kinematic analysis of throwing for handball player - The differences between using the sticking tape and the sticking gel - Ito, T.; Yukawa, H.; Sugimori, H.; Matsuki, Y.; Fukuda, J.; Suzuki, Y.; Hide, T.; Moriguchi, T. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
The purpose of this study was to reveal the difference of motion between using the sticking gel and the sticking tape, to propose the environmental improvement, and to provide the latest research based information for coaching young generations. As the results, there were differences of range of motion (ROM) for the maximum external rotation, the flexion of elbow, and the extension of wrist between two conditions while throwing the ball.